Analisis Profitabilitas, Leverage, dan Dewan Komisaris Pada Potensi Penghindaran Pajak (Studi Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019) - Nevia Octi Nilasari; Arisyahidin Arisyahidin (Universitas Islam Kadiri, 2021)
This study aims to determine the Effect of Profitability, Leverage and the Proportion of Independence Commissioner on Tax Avoidance (Study on Mining Companies Listed on the Indonesia Stock Exchange 2016-2019). The population is 192 financial data from 48 mining sector companies listed on the Indonesia Stock Exchange (IDX), while the determination of the sample used purposive sampling technique. The data collection used is documentation technique and literature study. The data collected were analyzed using the formula of each financial ratio, then processed using multiple regression analysis, coefficient of determination analysis, hypothesis testing and classical assumption testing.The results of multiple regression analysis show the equation Y = 0.519 -0.536 X1 - 0.049 X2 - 0.124 X3, which means that the ROA variable has a significant negative effect on CETR, with a coefficient of -0.536. This means that every 1% increase in ROA occurs, CETR will decrease by -0.536%, while DER has a significant negative effect on CETR with a coefficient of -0.049. This means that for every 1% increase in DER, the CETR will decrease by -0.049%. While the PKI had no significant effect on CETR.